Muamalah Bisnis Perdagangan Syariah - Ari Kurniawan (Universitas Muhammadiyah Surabaya, 2017)
Over the last few decades, the practice of Islamic trade has developed rapidly in Indonesia. This Muamalah transaction must both fulfill Islamic principle and implement Islamic contract. The product innovation in Islamic trade has also grown in the practice of Islamic business. This innovation relates to not only the business of Islamic finance but also the practice of Islamic retail trade. A good example would be Islamic top-up card and Sharia transportation service (Islamic “ojek”). Once Islamic trande implements Sharia‟ principle in these transactions, it has complied Islamic law. In contrast, when it has not implemented Sharia‟ principle in these business innovation, It has not been complied Sharia‟ law completely (kaffah). This article would analyze the compliance of these business in Islamic trade in Indonesia.